Selection of factitious hosts for three neotropical trichogrammatid species - Dias, Nivia da Silva; Parra, José Roberto Postali; Lima, Tiago Cardoso da Costa (Pesquisa Agropecuaria Brasileira, 2008)
The objective of this work was to assess the biological characteristics of the parasitoids Trichogrammatoidea annulata, Trichogramma atopovirilia e Trichogramma bruni, reared on factitious hosts, through different generations, in order to select the best host for parasitoid mass rearing. The experiment was carried out in a completely randomized design, in a 3x3 factorial arrangement (three hosts – Anagasta kuehniella, Corcyra cephalonica and Sitotroga cerealella – and three generations – 1st, 10th and 28th). Evaluations were made for: the total parasitized eggs by each female; viability; longevity of male and female; duration of the egg-adult period; sexual ratio; and viability of the parasitoids. The parasitoids Trichogrammatoidea annulata and Trichogramma bruni showed better development on C. cephalonica. For Trichogramma atopovirilia, the factitious host can be either C. cephalonica or A. kuehniella. The host S. cerealella was the least indicated for the three parasitoids species. The evaluated trichogrammatids showed adaptative capacity to their preferential factitious host, through generations.